Nanoencapsulation of saffron (Crocus sativus L.) extract in zein nanofibers and their application for the preservation of sea bass fillets. (15th June 2022) - Najafi, Zahra; Cetinkaya, Turgay; Bildik, Fatih; Altay, Filiz; Yeşilçubuk, Neşe Şahin
Abstract: In this study, saffron extract (SE) was encapsulated in zein nanofibers (ZNs) via electrospinning and then ZNs loaded with SE (ZNLSE) were applied as a nanocoating material. The effects of different zein concentrations (15%, 25%, and 30% w/v), SE concentrations (5% and 10% w/w) and the applied voltages on the morphology of ZNs were studied. The thermal stability of ZNs decreased with the addition of SE as determined by DSC. The molecular interaction between SE and zein was confirmed by ATR-FTIR. The encapsulation efficiency of crocins and picrocrocin, in ZNLSE (10%), were 64% and 47%, respectively assessed by HPLC. The antioxidant activity of ZNLSE (56.3%) was higher than that of the ZNs as assessed by ABTS method. Chemical deterioration in the control and coated fish fillets was monitored in terms of total volatile basic nitrogen (TVBN), thiobarbituric acid reactive substances (TBARS), peroxide value (PV), free fatty acid (FFA) and pH. The TVBN values of the treated samples were 30% lower than those of the control group on 8th day of cold storage. The results of this study indicated that ZNLSE has a significant potential as a coating material for prolonging the shelf lives of solid foods such as fish fillets. Graphical abstract: Image 1 Highlights: Molecular, thermal and morphological properties of produced nanofıbers were studied. Diameter of nanofıbers was affected by the applied voltage and amount of SE loading. Molecular interactions detected by FTIR, confirms the effective encapsulation of SE. ZNLSE containing 10% SE showed the highest antioxidant activity. Coating of the fish fillets extended their shelf life and delayed their spoilage.